Ultra-Small Lysozyme-Protected Gold Nanoclusters as Nanomedicines Inducing Osteogenic Differentiation - Li K (Dove Medical Press, 2020)
Kuo Li,1,* Pengfei Zhuang,1,2,* Bailong Tao,3 Dan Li,1,2 Xuejiao Xing,1 Xifan Mei1 1Department of Orthopedics, School of Pharmaceutical Science, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou, People’s Republic of China; 2Department of Basic Science, School of Pharmaceutical Science, Jinzhou Medical University, Jinzhou, People’s Republic of China; 3Key Laboratory of Biorheological Science and Technology, Ministry of Education College of Bioengineering, Chongqing University, Chongqing 400044, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xifan Mei Tel +86 13504064506Email meixifan@jzmu.edu.cnPurpose: Ultra-small gold nanoclusters (AuNCs), as emerging fluorescent nanomaterials with excellent biocompatibility, have been widely investigated for in vivo biomedical applications. However, their effects in guiding osteogenic differentiation have not been investigated, which are important for osteoporosis therapy and bone regeneration. Herein, for the first time, lysozyme-protected AuNCs (Lys-AuNCs) are used to stimulate osteogenic differentiation, which have the potential for the treatment of bone disease.Methods: Proliferation of MC3T3E-1 is important for osteogenic differentiation. First, the proliferation rate of MC3T3E-1 was studied by Cell Counting Kit-8 (CCK8) assays. Signaling pathways of PI3K/Akt play central roles in controlling proliferation throughout the body. The expression of PI3K/Akt was investigated in the presence of lysozyme, and lysozyme-protected AuNCs (Lys-AuNCs) by Western blot (WB) and intracellular cell imaging to evacuate the osteogenic differentiation mechanisms. Moreover, the formation of osteoclasts (OC) plays a negative role in the differentiation of osteoblasts. Nuclear factor κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) signaling pathways are used to understand the negative influence of the osteogenic differentiation by the investigation of Raw 264.7 cell line. Raw 264.7 (murine macrophage-like) cells and NIH/3T3 (mouse fibroblast) cells were treated with tyloxapol, and the cell viability was assessed. Raw 264.7 cells have also been used for in vitro studies, on understanding the osteoclast formation and function. The induced osteoclasts were identified by TRAP confocal fluorescence imaging. These key factors in osteoclast formation, such as (NFATc-1, c-Fos, V-ATPase-2 and CTSK), were investigated by Western blot.Results: Based on the above investigation, Lys-AuNCs were found to promote osteogenic differentiation and decrease osteoclast activity. It is noteworthy that the lysozyme (protected template), AuNPs, or the mixture of Lysozyme and AuNPs have negligible effects on osteoblastic differentiation compared to Lys-AuNCs.Conclusion: This study opens up a novel avenue to develop a new gold nanomaterial for promoting osteogenic differentiation. The possibility of using AuNCs as nanomedicines for the treatment of osteoporosis can be expected.Keywords: nanoclusters, bone, osteogenic differentiation, osteoporosis